Impact of built environment on walking in the case of Tehran, Iran. - (:unkn) unknown (Elsevier, 2021)
Growth of population, economic activities, and travel demand has resulted in serious problems, including air pollution, particularly in the large cities of developing countries. Many metropolitan areas are thus now seeking strategies to encourage the use of sustainable travel modes, which is significantly affected by built environment (BE). This study examines the impact of BE on walking choice and distance for discretionary trips, namely recreational and shopping trips for the case of Tehran, Iran. Circular buffer is used to explore characteristics of close neighborhoods, while transport-analysis-zone (TAZ) for wider neighborhoods.
Keywords: Iran; Teheran; Großstadt; Metropolregion; Gebaute Umwelt; Verkehrsmittelwahl; Fußgängerverkehr